2016
DOI: 10.1136/annrheumdis-2016-eular.3933
|View full text |Cite
|
Sign up to set email alerts
|

AB1001 Online Consultation for Chinese Patients with Rheumatic Diseases Based on Smart System of Disease Management (SSDM) Mobile Tools: A Study of Medical Economics

Abstract: BackgroundChina has no primary medical care and referral system. Patients can choose any hospitals or any doctors they like to seek medical care in China. As a result, most patients with rheumatic diseases rushed to a few large cities.Survey shows more than 40% of the rheumatic disease patients don't need to go to hospital and they only need advices from specialist.Smart System of Disease Management (SSDM) is a series of applications for chronic diseases management, which develop the interaction between doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Limited published works in the literature have focused on mHealth apps for AS management in China [ 7 , 27 ]. Although the Smart System of Disease Management (SSDM) was used for AS management, the characteristics and functions of the SSDM have not been clearly described in the literature [ 7 , 27 ]. Our search of app stores found that there are some publicly available apps for AS management despite limited published works.…”
Section: Introductionmentioning
confidence: 99%
“…Limited published works in the literature have focused on mHealth apps for AS management in China [ 7 , 27 ]. Although the Smart System of Disease Management (SSDM) was used for AS management, the characteristics and functions of the SSDM have not been clearly described in the literature [ 7 , 27 ]. Our search of app stores found that there are some publicly available apps for AS management despite limited published works.…”
Section: Introductionmentioning
confidence: 99%